2020
DOI: 10.1049/iet-bmt.2019.0196
|View full text |Cite
|
Sign up to set email alerts
|

PRNU‐based detection of facial retouching

Abstract: Nowadays, many facial images are acquired using smart phones. To ensure the best outcome, users frequently retouch these images before sharing them, e.g. via social media. Modifications resulting from used retouching algorithms might be a challenge for face recognition technologies. Towards deploying robust face recognition as well as enforcing anti-photoshop legislations, a reliable detection of retouched face images is needed. In this work, the effects of facial retouching on face recognition are investigate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 38 publications
1
31
0
Order By: Relevance
“…• In a single image scenario, in which only a potentially manipulated image is processed by the detection system, the detection performance can highly depend on the quality of the manipulated image as well as applied image post-processing. It was found that image compression can severely impact face recognition performance [35] as well as retouching detection methods [17], [19]. Similar effects are to be expected for other types of postprocessing, e.g.…”
Section: Related Worksupporting
confidence: 61%
See 4 more Smart Citations
“…• In a single image scenario, in which only a potentially manipulated image is processed by the detection system, the detection performance can highly depend on the quality of the manipulated image as well as applied image post-processing. It was found that image compression can severely impact face recognition performance [35] as well as retouching detection methods [17], [19]. Similar effects are to be expected for other types of postprocessing, e.g.…”
Section: Related Worksupporting
confidence: 61%
“…Among other image manipulation techniques, such as geometric distortion or morphing, they reported significant performance degradation for various facial recognition systems after the application of strong facial retouching. These findings have been confirmed by Bharati et al [15], [16] while Rathgeb et al [19] showed that face recognition systems might be robust to the application of moderate facial retouching.…”
Section: Related Workmentioning
confidence: 58%
See 3 more Smart Citations